Manganese Superoxide Dismutase Dysfunction and the Pathogenesis of Kidney Disease - Kitada, Munehiro; Xu, Jing; Ogura, Yoshio; Monno, Itaru; Koya, Daisuke (Frontiers in Physiology, 2020)
The mitochondria are a major source of reactive oxygen species (ROS). Superoxide anion (O2•−) is produced by the process of oxidative phosphorylation associated with glucose, amino acid, and fatty acid metabolism, resulting in the production of adenosine triphosphate (ATP) in the mitochondria. Excess production of reactive oxidants in the mitochondria, including O2•−, and its by-product, peroxynitrite, that is generated by a reaction between O2•− with nitric oxide (NO•), alters cellular function via oxidative modification of proteins, lipids, and nucleic acids. Mitochondria maintain an antioxidant enzyme system that eliminate excess ROS; manganese superoxide dismutase (Mn-SOD) is one of the major components of this system as it catalyzes the first step involved in scavenging ROS. Reduced expression and/or the activity of Mn-SOD results in diminished mitochondrial antioxidant capacity; this can impair the overall health of the cell by altering mitochondrial function and may lead to the development and progression of kidney disease. Targeted therapeutic agents may protect mitochondrial proteins including Mn-SOD against oxidative stress-induced dysfunction, and this may consequently lead to protection of renal function. Here, we describe the biological function and regulation of Mn-SOD, and review the significance of mitochondrial oxidative stress with respect to the pathogenesis of kidney diseases, including chronic kidney disease (CKD) and acute kidney injury (AKI), with a focus on Mn-SOD dysfunction..